Identification and dipeptidyl peptidase IV (DPP-IV) inhibitory activity verification of peptides from mouse lymphocytes - Juan Wang; Yujia Xie; Yuanyuan Luan; Tingting Guo; Shanshan Xiao; Xingxing Zeng; Shaohui Zhang (Food Science and Human Wellness)
The objective of this study was to isolate and identify the intracellular bioactive peptides from mouse lymphocytes before and after lipopolysaccharide (LPS) stimulation, to explore novel peptides and to research the bioactive function. Mouse spleen lymphocytes were isolated and cultured with LPS stimulation (experimental group) or not (control group) to collect intracellular peptides. Totally 385 peptides were analyzed by nanoliter liquid phase-Q Exactive quadrupole ultra-high resolution orbitrap mass spectrometer (Nano LC-Q Exactive Plus) and identified by PEAKS X software. After compared with peptides reported, 131 novel peptides were discovered, which then were predicted bioactivity by Peptide Ranker and 6 peptides with high bioactivity were predicted function by BIOPEP-UMW database. Prediction data showed that they may have dipeptidyl peptidase IV (DPP-IV) inhibitory activity. Finally, two peptides showed better potent inhibition were verified with competitive and noncompetitive modes.